An experimental and modeling study on apparent bending moduli of cross-laminated bamboo and timber (CLBT) in orthogonal strength directions. (June 2022) - Li, Hao; Wang, Brad Jianhe; Wang, Libin; Wei, Yang
Abstract: In this paper, the bending properties of a 3-ply cross-laminated bamboo and timber (CLBT), prefabricated with the bamboo mat-curtain panel and hem-fir lumber, were examined in the major and minor strength directions, and a 3-ply hem-fir cross-laminated timber (CLT) was taken as a control group. The analytical model for the sum of the orthogonal apparent bending moduli with the two types of layer classifications were proposed, and the two kinds of contribution models were developed to analyze the apparent bending modulus variation behavior of the CLBT and CLT panels in the major and minor strength directions. The experimental results showed that since the CLBT group had more internal orthogonal structures, its difference in the bending properties between the major and minor strength directions was lower than that of the CLT group. Furthermore, the proposed contribution models quantitatively analyzed the relationship between the apparent bending moduli of the CLBT and CLT panels and the corresponding composition layer characteristics. The contribution model to characterize the apparent bending modulus in major and minor strength directions demonstrated good agreement with the test results. Based on this model interpreted by three-dimensional figures, the contribution variation characteristics in the major and minor strength directions were revealed.